2019
DOI: 10.1371/journal.pntd.0007400
|View full text |Cite
|
Sign up to set email alerts
|

A novel integrated molecular and serological analysis method to predict new cases of leprosy amongst household contacts

Abstract: Background Early detection of Mycobacterium leprae is a key strategy for disrupting the transmission chain of leprosy and preventing the potential onset of physical disabilities. Clinical diagnosis is essential, but some of the presented symptoms may go unnoticed, even by specialists. In areas of greater endemicity, serological and molecular tests have been performed and analyzed separately for the follow-up of household contacts, who are at high risk of developing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 45 publications
1
26
0
1
Order By: Relevance
“…M. leprae DNA detection frequency in HHC from Bangladesh (12.3% in SSS and 18.0% in NS) was in line with previous studies conducted in several hyperendemic areas of Brazil, Colombia and Indonesia (45,(47)(48)(49)(50). In India higher positivity (21%) in SSS of HHC was reported (38) whereas in a Brazilian study from Uberlandia, up to 49% of positivity in NS was observed (12).…”
Section: Discussionsupporting
confidence: 88%
“…M. leprae DNA detection frequency in HHC from Bangladesh (12.3% in SSS and 18.0% in NS) was in line with previous studies conducted in several hyperendemic areas of Brazil, Colombia and Indonesia (45,(47)(48)(49)(50). In India higher positivity (21%) in SSS of HHC was reported (38) whereas in a Brazilian study from Uberlandia, up to 49% of positivity in NS was observed (12).…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest that household contact should be monitored for putative subclinical infection. This hypothesis was further confirmed in a 6 years’ follow-up study demonstrating that a long time some household contacts developed leprosy disease [ 28 ]. Therefore, the significant level of antigen-specific cytokine secretion by peripheral blood cells of household contacts, especially those HHC(MB), described in the present investigation, provides reliable evidence of their higher susceptibility to leprosy disease.…”
Section: Discussionmentioning
confidence: 75%
“…This is a robust multivariate analysis, able to build classification trees with minimal error rates, which is favorable for the diagnosis of diseases such as leprosy 56,57 . 55 , used the classification model "Sick × Healthy" in the Random Forest analysis based on serological, molecular, and bacilloscopic data, to evaluate the prediction of infection in clinically diagnosed cases and household contacts, accompanying them for five years. This model, Random Forest, highlighted the possibility of early diagnosis of MB (90.5%) and especially PB (70.6%) cases, while separately evaluated tests did not reach the same high rate of diagnostic correctness.…”
Section: Contact Surveillance: Importance Of Molecular and Serologicamentioning
confidence: 99%
“…In areas of greater endemicity, serological and molecular tests have been carried out and analyzed separately. However, Gama et al (2019) 55 proposed the integration of these methods to assist in the diagnosis and monitoring of household contacts using the Random Forest algorithm for data analysis. This is a robust multivariate analysis, able to build classification trees with minimal error rates, which is favorable for the diagnosis of diseases such as leprosy 56 , 57 .…”
Section: Contact Surveillance: Importance Of Molecular and Serologicamentioning
confidence: 99%